Information and Communications Technology (ICT) Competency and Capability of Sauyo High School Teachers: A Basis for ICT Development Plan - MALANGEN, ARDRIAN; ISORENA, JEFFERSON (International Journal of Arts, Sciences and Education, 2022)
The Philippines opted to embrace globalization in the mid-1990s as it set out to address globalization’s challenges. This comes with the need to maintain the current education in the Philippines. The purposed of the study is to determine the Information and Communications Technology (ICT) Competency and Capability of Sauyo High School Teachers: A Basis for ICT Development Plan. A total of 112 teachers random-purposive sampling involved in the study. The study utilized a descriptive correlational method. Based on the results of the study the teacher respondents are predominantly 31-40 years old, female, earned a master’s unit, and had attended 1-3 years of ICT training. The Level of ICT Competency of Sauyo High School Teachers is Proficient. The Level of ICT Capability of Sauyo High School is Very Satisfactory. There is no significant difference on the level of ICT competency of Teachers and on the level of ICT capability of Sauyo High School as perceived by the teachers when grouped according to profile. There is a significant moderately positive relationship between the level of ICT Competency of teachers and the level of ICT Capability of Sauyo High School as perceived by the teachers. Thus, the following are recommended in this study. Skills enhancement training on ICT use in teacher professional development is conducted. The training providers should refer to any existing competency standards. Department of Education (DepEd) should provide a mechanism for strengthening secondary teachers’ ICT competence by integrating ICT training in the In-Service Training (INSET) of teachers anchored on the skill-set and basic competence to introduce their ICT skills further the-Advance meaningful ICT integrated teaching-learning to students.